Preliminary Evidence for Enhanced Thymine Absorption: A Putative New Phenotype Associated With Fluoropyrimidine Toxicity in Cancer Patients. Issue 4 (August 2018) - Duley, John A.; Ni, Ming; Shannon, Catherine; Norris, Ross L.; Sheffield, Leslie; Cowley, David; Harris, Marion; van Kuilenburg, André B. P.; Helsby, Nuala; George, Rani; Charles, Bruce G.
Abstract : Background: Chemotherapy for colorectal, head and neck, and breast cancer continues to rely heavily on 5-fluorouracil and its oral prodrug capecitabine. Associations of serious fluoropyrimidine adverse effects have focused on inherited deficiency of the catabolic enzyme, dihydropyrimidine dehydrogenase. However, abnormal dihydropyrimidine dehydrogenase activity accounts for only about one-third of observed toxicity cases. Thus, the cause of most fluorouracil toxicity cases remains unexplained. Methods: For this small cohort study, thymine (THY) 250 mg was administered orally to 6 patients who had experienced severe toxicity during treatment with 5FU or capecitabine. Plasma and urine were analyzed for THY and its catabolites dihydrothymine (DHT) and β-ureidoisobutyrate. Results: Of the 6 patients, 2 had decreased THY elimination and raised urinary THY recovery consistent with inherited partial dihydropyrimidine dehydrogenase deficiency, confirmed by DPYD sequencing. Unexpectedly, 3 patients displayed grossly raised plasma THY concentrations but normal elimination profiles (compared with a normal range for healthy volunteers previously published by the authors). DPYD and DPYS sequencing of these 3 patients did not reveal any significant loss-of-activity allelic variants. The authors labeled the phenotype in these 3 patients as "enhanced thymine absorption". Only 1 of the 6 cases of toxicity had a normal postdose plasma profile for THY and its catabolites. Postdose urine collections from all 6 patients had THY/DHT urinary ratios above 4.0, clearly separated from the ratios in healthy subjects that were all below 3.0. Conclusions: This small cohort provided evidence for a hypothesis that fluorouracil toxicity cases may include a previously undescribed pyrimidine absorption variant, "enhanced thymine absorption, " and elevated THY/DHT ratios in urine may predict fluorouracil toxicity. A prospective study is currently being conducted.